2017
DOI: 10.14434/sdh.v1i2.23251
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Photogrammetry in Greek Archaeology

Abstract: This paper addresses the advantages as well as the obstacles in practicing photogrammetry based on archival photos of archaeological sites and examines how the results can be put to use for further research, preservation, restoration and monitoring rates of deterioration. While the extensive use of historic aerial photographs has been applied to photogrammetric modeling, archaeological excavation archives have been largely ignored. Historically, archaeological excavations have been vigorosly documented photogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…The decreasing cost and wider availability of both declassified historic satellite photographs and high-resolution multi-spectral satellite imagery have begun to allow us to identify thousands of new archaeological sites at large scales -in some cases in areas spanning tens or even hundreds of thousands of square kilometers (Casana 2014;Parcak 2009;Parcak 2019;Ur 2003Ur , 2006Ur , 2010. Advances in photogrammetric tools and techniques enable processing of large historical aerial survey collections, enabling the production of high resolution 3D models, orthomosaics, and digital elevation models over large areas, which in turn enables detection and analysis of archaeological features that have since been destroyed or that have degraded considerably since the aerial photographs were taken (Wallace 2017).…”
Section: Virtual Archaeology: Epistemological and Methodological Considerationsmentioning
confidence: 99%
“…The decreasing cost and wider availability of both declassified historic satellite photographs and high-resolution multi-spectral satellite imagery have begun to allow us to identify thousands of new archaeological sites at large scales -in some cases in areas spanning tens or even hundreds of thousands of square kilometers (Casana 2014;Parcak 2009;Parcak 2019;Ur 2003Ur , 2006Ur , 2010. Advances in photogrammetric tools and techniques enable processing of large historical aerial survey collections, enabling the production of high resolution 3D models, orthomosaics, and digital elevation models over large areas, which in turn enables detection and analysis of archaeological features that have since been destroyed or that have degraded considerably since the aerial photographs were taken (Wallace 2017).…”
Section: Virtual Archaeology: Epistemological and Methodological Considerationsmentioning
confidence: 99%
“…On most occasions, these data transformations are made with a view to enhancement, reanalysis or re-interpretation using novel IT tools and methods. Such aspects include studies in the grey literature [8], excavation datasets [9][10][11][12][13], survey and CRM records [14][15][16][17][18][19], archival material [20], retrospective photogrammetry [21,22], and data harvesting and modelling [23,24].…”
Section: Studying Digital Legaciesmentioning
confidence: 99%
“…Revisiting archival sources, archaeologists are beginning to demonstrate the value of old excavation photographs for contextualizing contemporary excavations in 3D. From case studies in Greece, Wallace (2017) demonstrated how using photographs from as far back as the 1970s to generate models provides a useful baseline for conducting archaeological work today. The use of old photographs was also productive for Paleolithic excavations, which often revisit the same sites and benefit from improved spatial context derived from archival photographs (Discamps et al 2016).…”
Section: Ground-based Photogrammetrymentioning
confidence: 99%